Sari Sarna (santhal religion) - Hembram,P. C. (Delhi, 1988)
"SARI-SARNA" describes the traditional mandates of Santhal community which has been established after thou sand years experiment in different geographical regions since dateless past. It is not a religion in the strict sense as we understand from philosophical point of view but a way of social and cultural life of the community. The whole development goes through a process of evolution right from the creation of earth, man and their numeration, settlement and peaceful organised life. The terminologies used in traditional practices have been analysed minutely to understand the source of inspiration that this major linguistic tribal group of India respond to it to maintain the Community solidarity and identity.
Keywords: Tribes India